The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/ar.a.20354
|View full text |Cite
|
Sign up to set email alerts
|

Clavicle, a neglected bone: Morphology and relation to arm movements and shoulder architecture in primates

Abstract: In spite of its importance for movements of the upper limbs, the clavicle is an infrequently studied shoulder bone. The present study compares clavicular morphology among different extant primates. Methods have included the assessment of clavicular curvatures projected on two perpendicular planes that can be assessed overall as cranial and dorsal primary curvatures. Results showed that in cranial view, three morphologies can be defined. One group exhibited an external curvature considerably more pronounced tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 43 publications
10
56
0
Order By: Relevance
“…333x-6/9 is distinct from other hominoids in the orientation of its lateral end (on frontal view) and in the position of the deltoid attachment area, features which he interpreted as evidence of descent of the hominin shoulder by three to four million years ago. However, in his analysis of clavicular shape in primates, Voisin 16 reports that the uniquely low shoulder position in humans is indicated, on dorsal view, by a distinctive curvature of the medial rather than the lateral end of the human clavicle. Although A.L.…”
Section: Early Homininsmentioning
confidence: 99%
“…333x-6/9 is distinct from other hominoids in the orientation of its lateral end (on frontal view) and in the position of the deltoid attachment area, features which he interpreted as evidence of descent of the hominin shoulder by three to four million years ago. However, in his analysis of clavicular shape in primates, Voisin 16 reports that the uniquely low shoulder position in humans is indicated, on dorsal view, by a distinctive curvature of the medial rather than the lateral end of the human clavicle. Although A.L.…”
Section: Early Homininsmentioning
confidence: 99%
“…Understanding the evolutionary process of these features is pivotal for the study of living hominoid evolution. Numerous studies have examined hominoid skeletal morphology in the forelimb, shoulder girdle and vertebral column (Cartmill and Milton 1977;Larson 1988Larson , 1998Rose 1988Rose , 1989Takahashi 1990;Gebo 1993Gebo , 1996Ward 1993;Voisin 2006). However, comparatively fewer morphological studies have been undertaken on the living (Schultz 1956(Schultz , 1961Erikson 1963;Ohman 1986;Gebo 1996;Chan 1997;Preuschoft et al 2003) and fossil (Schultz 1960;Schmid 1983Schmid , 1991Jellema et al 1993;Moyà-Solà et al 2004;Sawyer and Maley 2005) hominoid thoracic region.…”
Section: Introductionmentioning
confidence: 99%
“…One essential, and unique, feature, compared to other laboratory animals, was the presence of a clavicle that enabled movements of the upper limb similar to humans. 24 Furthermore, the pectoral implantation site of the IPM in the baboons compared very well with those of humans. The material density of the Pectoralis major muscle of 1.115 ± 0.055 g/cm 3 of this study, determined on freshly excised tissue, compared well with previously reported values for mammalian muscle tissue of 1.112 ± 0.006 g/cm 3 , measured on muscle tissue after fixation in 4% formaldehyde.…”
Section: Discussionmentioning
confidence: 85%